Construction and analysis for dys-regulated lncRNAs and mRNAs in LPS-induced porcine PBMCs. Issue 2 (February 2021) - Zhang, Jing; Xu, Xin; Chen, Hongbo; Kang, Ping; Zhu, Huiling; Ren, Hongyan; Liu, Yulan
Long non-coding RNAs (lncRNAs) are emerging as key regulators in inflammation. However, their functions and profiles in LPS-induced inflammation in pigs are largely unknown. In this study, we profiled global lncRNA and mRNA expression changes in PBMCs treated with LPS using the lncRNA-seq technique. In total 43 differentially expressed (DE) lncRNAs and 1082 DE mRNAs were identified in porcine PBMCs after LPS stimulation. Functional enrichment analysis on DE mRNAs indicated these genes were involved in inflammation-related signaling pathways, including cytokine–cytokine receptor interaction, TNF-α, NF-κB, Jak-STAT and TLR signaling pathways. In addition, co-expression network and function analysis identified the potential lncRNAs related to inflammatory response and immune response. The expressions of eight lncRNAs (ENSSSCT00000045208, ENSSSCT00000051636, ENSSSCT00000049770, ENSSSCT00000050966, ENSSSCT00000047491, ENSSSCT00000049750, ENSSSCT00000054262 and ENSSSCT00000044651) were validated in the LPS-treated PBMCs by quantitative real-time PCR (qRT-PCR). In LPS-challenged piglets, we identified that expression of three lncRNAs (ENSSSCT00000051636, ENSSSCT00000049770, and ENSSSCT00000047491) was significantly up-regulated in liver, spleen and jejunum tissues after LPS challenge, which indicated that these lncRNAs might be important regulators for inflammation. This study provides the first lncRNA and mRNA transcriptomic landscape of LPS-mediated changes in porcine PBMCs, which might provide potential insights into lncRNAs involved in regulating inflammation in pigs.